Estudio de tiempos y movimientos en el proceso de encartonado de blíster e influencia en el ciclo de producción en una empresa farmacéutica - Escobar Vera, Luis Manuel (2017)
Good manufacturing practices are pillars for the pharmaceutical industry, giving guaranteed guidelines for the customer with a high quality product. The present research work is a study of times and movements to improve the efficiency in the manufacturing processes, in the area of paneling, it is for this reason that the investigation of each of the activities that make up the process is carried out, giving factors and Established times for each of the macro, micro and its methods that have been established by the industry and taken in each of the processes. In the process there are costs for dead time, which do not provide quality to the product, it is for this reason that is based on the method of study of times and movements, for the standardization of production lines in the industry. These lines are semiautomatic, so time measurement techniques are used to analyze efficiency levels and thus determine a maximum yield of 90% to 95% of productivity required by the company, through the established times for the process of inking and Evaluating the activities....